Study on the axial stress of angle steel components of transmission tower. Issue 1 (June 2020) - Yu, Xinmin; Fu, Benzhao; Xie, Ming
Abstract: Taking the common specifications of the transmission tower as equal angle steel as the research object, for the angle steel of different specifications, based on the theory of equal strength, the critical slenderness ratio and the critical calculated length of each angle steel under the arrangement of parallel axis and minimum axis and Q345 and Q420 materials The critical slenderness ratio and critical calculated length of each angle steel under the minimum axis arrangement, and by simplifying the economic index, comparing the stability coefficient and stable bearing capacity of the angle steel under the same conditions, analyzing the economics of the angle steel, and finally proposing In the design of the line pole tower, the method of selecting angle steel reasonably.